BRAND PROTECTION FOR MSMES IN ENCOURAGING ECONOMIC GROWTH IN INDONESIA - Tribuana, Robi Rendra; Lubis, Riyani Fitri (Yurisprudentia: Jurnal Hukum Ekonomi, 2024)
This research seeks to analyze the significance of brand protection for Micro, Small, and Medium Enterprises (MSMEs) in encouraging economic growth in Indonesia. Through a normative juridical approach, this research identifies brand protection as the key to strengthening the position of MSMEs in a competitive market. By providing adequate brand protection, MSMEs can build reputation, increase competitiveness, and expand access to markets and financial resources. However, challenges such as a lack of understanding about brand protection, the complexity of the registration process, and high costs need to be overcome through educational approaches, process simplification, and incentives for MSMEs. Thus, brand protection will not only provide direct benefits for MSMEs but will also contribute to inclusive and sustainable economic growth in Indonesia.